Experiences of Thai Rural Women Sustaining Self-Care in Midlife: A Phenomenological Study - Arpanantikul, Manee; Lumdubwong, Aporacha; Unsanit, Pennapa; Rujiwatthanakorn, Dolrat; Pornsinsiriruck, Sarwitree; Boonrin, Pacharin (Pacific Rim International Journal of Nursing Research, 2020)
With having responsibility for many competing demands in work and homelife, middle aged women often do not have time or energy for important self-care. The purpose of this study was to investigate ways to sustain self-care from the experience of Thai middle-aged women living in the community. This study employed a hermeneutic phenomenological approach and the philosophy of the sufficiency economy to understand the experiences of 20 Thai middle-aged women living in a central agricultural community. Data collection were conducted between 2014 and 2015 through in-depth, recorded interviews, field notes, and participant observation. All interviews were transcribed verbatim and data were analyzed using hermeneutic analysis. The findings showed ways to sustaining self-care of Thai middle-aged women consisting of 7 themes: 1) having determination, 2) having a model, 3) developing a leader, 4) continuing to be involved with self-care activities, 5) setting up rules, 6) building self-care culture, and 7) developing a self-care group/network. The findings of this study suggest that in order to achieve self-care sustainability women should get to know themselves, have intention and belief, together with having power of community and support. Therefore, having self-care constantly will help prevent disease and promote healthy in women’s lives. Nurses can play an active role in motivating and supporting women to attain and maintain self-care behaviours which result in having better health and good quality of life.